The relationship between moral distress, burnout, and considering leaving a hospital job during the COVID-19 pandemic: a longitudinal survey - Robert G. Maunder; Natalie D. Heeney; Rebecca A. Greenberg; Lianne P. Jeffs; Lesley A. Wiesenfeld; Jennie Johnstone; Jonathan J. Hunter (BMC, 2023)
Abstract Background Previous research suggests that moral distress contributes to burnout in nurses and other healthcare workers. We hypothesized that burnout both contributed to moral distress and was amplified by moral distress for hospital workers in the COVID-19 pandemic. This study also aimed to test if moral distress was related to considering leaving one's job. Methods A cohort of 213 hospital workers completed quarterly surveys at six time-points over fifteen months that included validated measures of three dimensions of professional burnout and moral distress. Moral distress was categorized as minimal, medium, or high. Analyses using linear and ordinal regression models tested the association between burnout and other variables at Time 1 (T1), moral distress at Time 3 (T3), and burnout and considering leaving one's job at Time 6 (T6). Results Moral distress was highest in nurses. Job type (nurse (co-efficient 1.99, p < .001); other healthcare professional (co-efficient 1.44, p < .001); non-professional staff with close patient contact (reference group)) and burnout-depersonalization (co-efficient 0.32, p < .001) measured at T1 accounted for an estimated 45% of the variance in moral distress at T3. Moral distress at T3 predicted burnout-depersonalization (Beta = 0.34, p < .001) and burnout-emotional exhaustion (Beta = 0.38, p < .008) at T6, and was significantly associated with considering leaving one's job or healthcare. Conclusion Aspects of burnout that were associated with experiencing greater moral distress occurred both prior to and following moral distress, consistent with the hypotheses that burnout both amplifies moral distress and is increased by moral distress. This potential vicious circle, in addition to an association between moral distress and considering leaving one's job, suggests that interventions for moral distress may help mitigate a workforce that is both depleted and burdened with burnout.